Agriculture waste reinforced corn starch-based biocomposites: effect of rice husk/walnut shell on physicomechanical, biodegradable and thermal properties. (28th January 2019) - Singh, Tej; Gangil, Brijesh; Patnaik, Amar; Biswas, Don; Fekete, Gusztáv
Abstract: In the present work, agriculture waste based biocomposites were developed by reinforcing corn starch resin with various rice husk and walnut shell content of 5, 10 and 15 wt%. These fabricated biocomposites were investigated for physical, mechanical and thermal properties. It was found that the physical properties such as density and water absorption of the biocomposites remains in the range of 1.20–1.32 g cm −3 and 4.32%–8.68% respectively, while these properties decreased by the increase of rice husk and walnut shell content. The slower degradation rate of rice husk and walnut shell resulted in enhanced degradation period of the biocomposites. Thermogravimetric analysis revealed that the addition of increased rice husk and walnut shell content enhanced the thermal stability of the biocomposites. The evaluated mechanical (tensile strength, flexural strength, compressive strength, impact energy and hardness) properties were found to increase with the amount of rice husk and walnut shell content. The maximum tensile strength of 10.70 MPa, flexural strength of 19.60 MPa and impact energy of 0.362 J was observed for biocomposites with 15 wt% rice husk content. Similarly, the maximum compressive strength of 22.70 MPa and hardness of 21.31 Hv is obtained for biocomposites with 15 wt% walnut shell content. The rice husk based biocomposites gave better tensile strength, flexural strength, impact energy and thermal stability but resulted in lower hardness and compressive strength than the walnut shell based biocomposites. The biocomposites reinforced with walnut shell exhibit higher resistance to water absorption and biodegradability than those associated with rice husk. The results suggest that the developed biocomposites can be used as ecofriendly materials in lightweight applications.